The Effect of Service Strategy and Corporate Image on Customers’ Decisions to Use Forwarding Services: An Empirical Study - Putri Wulan Fortuna; Amin Mansur (SAN Scientific, 2026)
The rapid growth of the logistics and freight forwarding industry has intensified competition, requiring companies to understand the key factors influencing customers' decisions in selecting forwarding services. However, empirical evidence on these determinants, particularly in Jakarta, remains limited. Therefore, this study aims to examine the influence of service quality, company image, price perception, and location on customers' decisions to use freight forwarding services at PT. Indonesian Freight Liner. This study employs a quantitative approach using multiple linear regression analysis. Primary data were collected through questionnaires distributed to 110 respondents who had used freight forwarding services. Data quality was assessed using validity and reliability tests, while classical assumption tests included normality, multicollinearity, and heteroscedasticity. Hypothesis testing was conducted using multiple linear regression, the coefficient of determination test, the t-test, and the F-test. The results indicate that service quality and company image have a positive and significant effect on customers' decisions. Meanwhile, price perception and location do not significantly influence decisions. These findings highlight the importance of service performance and corporate reputation in strengthening competitiveness in the freight forwarding industry.